INTRODUCTION TO LEADERSHIP Concepts and Practice - Northouse, Peter G. (SAGE Publications, Inc., 2021)
The Fifth Edition of Peter G. Northouse's bestselling Introduction to Leadership: Concepts and Practice provides readers with a clear, concise overview of the complexities of practicing leadership and concrete strategies for becoming better leaders. The text is organized around key leader responsibilities such as creating a vision, establishing a constructive climate, listening to outgroup members, and overcoming obstacles. Case studies, self-assessment questionnaires, observational exercises, and reflection and action worksheets engage readers to apply leadership concepts to their own lives. Grounded in leadership theory and the latest research, the fully updated, highly practical Fifth Edition includes a new chapter on destructive leadership, new cases, and new Leadership Snapshots.